Modified zirconium phosphate / resin composite material and preparation method thereof, and method for recovering nuclides in nuclear waste liquid

By using modified zirconium phosphate/resin composites, the problems of low selectivity of existing adsorption materials for nuclear waste liquids and poor adsorption recovery and desorption regeneration are solved, and efficient and stable nuclide adsorption recovery and desorption regeneration are achieved.

CN119114034BActive Publication Date: 2025-03-18JIANGSU HELPER FUNCTIONAL MATERIALS

Patent Information

Application Number
CN202411529437.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-18
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing adsorbent materials have low selectivity for nuclides in nuclear waste liquid, poor adsorption and recovery performance, and the desorption and regeneration process is complicated and incomplete.

Method used

A modified zirconium phosphate/resin composite material is used, which consists of modified zirconium phosphate and resin material containing doped metal ions. It is prepared by hydrothermal method, and has excellent nuclide selectivity and adsorption recovery performance, and has good desorption and regeneration performance.

Benefits of technology

The modified zirconium phosphate/resin composite has excellent adsorption and recovery performance for nuclides, and maintains the stability of structure and performance in multiple adsorption-regeneration cycles, significantly improving the efficiency and safety of nuclide recovery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114034B_ABST
    Figure CN119114034B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of adsorption materials, and specifically to a modified zirconium phosphate / resin composite material and a preparation method thereof, and a method for recovering nuclides in nuclear waste liquid. The modified zirconium phosphate / resin composite material of the present application comprises a modified zirconium phosphate and a resin material in a mass ratio of 1: (0.05-0.2), wherein the modified zirconium phosphate is a zirconium phosphate containing doped metal ions, and the doped metal ions include Cu 2+ , Fe 3+ 、Zn 2+ 、Co 2+ and Ni 2+ The modified zirconium phosphate / resin composite material provided in the present application has excellent selectivity for nuclides, so it has excellent adsorption recovery performance and good desorption regeneration performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of adsorption materials, and in particular to a modified zirconium phosphate / resin composite material and a preparation method thereof, and a method for recovering nuclides in nuclear waste liquid. Background Art

[0002] Nuclear energy has been widely developed due to its advantages of high energy density, clean and low carbon. However, a large amount of nuclear waste liquid will be produced during the circulation and reprocessing of nuclear fuel. The radionuclides included in the nuclear waste liquid pose a potential hazard to human life and the ecological environment. Therefore, capturing radionuclides to recover radioactive nuclides plays an important role in reducing the radioactivity level of nuclear waste liquid and reducing the impact on the environment and public health.

[0003] At present, adsorption materials are mainly used to recover radionuclides in nuclear waste liquid. Traditional adsorption materials mainly include activated carbon, ion exchange resins, metal organic frameworks (MOFs), clay minerals and other materials. The above materials all have relatively rich pore structures and can effectively provide adsorption sites. However, the above materials can adsorb multiple substances (including non-nuclide particles, etc.) at the same time, and have low selectivity for radionuclides, so the adsorption and recovery performance of radionuclides is poor. In addition, the desorption and regeneration process of the above materials is complicated and incomplete, and the regeneration performance is poor. Summary of the invention

[0004] Based on this, the present application provides a modified zirconium phosphate / resin composite material and a preparation method thereof, and a method for recovering nuclides in nuclear waste liquid. The modified zirconium phosphate / resin composite material provided in the present application has excellent selectivity for nuclides, so it has excellent adsorption recovery performance and good desorption regeneration performance.

[0005] In a first aspect of the present application, a modified zirconium phosphate / resin composite material is provided, wherein the modified zirconium phosphate / resin composite material comprises a modified zirconium phosphate and a resin material in a mass ratio of 1: (0.05-0.2); wherein the modified zirconium phosphate is a zirconium phosphate containing doped metal ions, and the doped metal ions include Cu 2+ , Fe 3+ 、Zn 2+ 、Co 2+ and Ni 2+ One or more of .

[0006] In one embodiment, the molar ratio of the doped metal ions to the zirconium ions in the zirconium phosphate is 1:(0.5-5).

[0007] In one embodiment, the resin material includes one or more of polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride, polystyrene and polyetheretherketone.

[0008] In one embodiment, the doping metal ions include Zn 2+ .

[0009] The second aspect of the present application provides a method for preparing the modified zirconium phosphate / resin composite material according to any one of the embodiments of the first aspect of the present application, comprising the following steps:

[0010] Mixing a zirconium source, a phosphate source and a doping metal salt in a dispersant by a hydrothermal method, and performing a reflux reaction to prepare a mixed solution, wherein the doping metal salt includes the doping metal ion;

[0011] After the mixed liquid is separated into solid and liquid, the solid phase is collected, and after the solid phase is washed, the modified zirconium phosphate is prepared;

[0012] The modified zirconium phosphate is mixed in a solvent, and a pore-forming agent and the resin material are added to prepare a mixed slurry, wherein the mass ratio of the modified zirconium phosphate to the resin material is 1: (0.05-0.2);

[0013] The mixed slurry is extruded to prepare the modified zirconium phosphate / resin composite material.

[0014] In one embodiment, the process parameters for the reflux reaction include: reaction temperature ≥ boiling point of the dispersant, and reaction time is 6h~18h.

[0015] In one embodiment, the steps of preparing the mixed solution have one or more of the following characteristics:

[0016] (1) The zirconium source includes one or more of zirconium oxychloride, zirconium acetate, zirconium silicate, zirconium sulfate and zirconium chloride;

[0017] (2) The phosphoric acid source includes one or more of sodium dihydrogen phosphate, ammonium dihydrogen phosphate, potassium dihydrogen phosphate, phosphorous acid, triethyl phosphate and sodium phosphate;

[0018] (3) The doped metal salt includes one or more of copper sulfate, iron sulfate, zinc sulfate, cobalt sulfate and nickel sulfate;

[0019] (4) The molar ratio of the zirconium source, the phosphoric acid source and the doping metal salt is 1:(1-6):(1-5);

[0020] (5) The dispersant includes one or more of water, ethanol, methanol, dimethyl sulfoxide and N,N-dimethylformamide;

[0021] (6) The mass ratio of the zirconium source and the dispersant is 1:(8-16).

[0022] In one embodiment, the step of preparing the mixed slurry has one or more of the following characteristics:

[0023] (1) The mass ratio of the modified zirconium phosphate to the solvent is 1:(1-8);

[0024] (2) The solvent includes one or more of water, ethanol, methanol, dimethyl sulfoxide and N,N-dimethylformamide;

[0025] (3) The pore-forming agent includes one or more of Tween 80, sodium bicarbonate, sodium chloride and polyethylene glycol;

[0026] (4) The resin material includes one or more of polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride, polystyrene and polyetheretherketone;

[0027] (5) The mass ratio of the modified zirconium phosphate to the pore-forming agent is 1:(0.03-0.15).

[0028] In a third aspect of the present application, a method for recovering nuclides in nuclear waste liquid is provided, comprising the following steps:

[0029] The modified zirconium phosphate / resin composite material described in any one of the embodiments of the first aspect of the present application is used to adsorb and treat nuclear waste liquid.

[0030] In one embodiment, the step of adsorbing the nuclear waste liquid has one or more of the following characteristics:

[0031] (1) The pH of the nuclear waste liquid is 6 to 9;

[0032] (2) The nuclear waste liquid contains one or more of rubidium ions and cesium ions;

[0033] (3) The process parameters of the adsorption treatment include: the flow rate of the nuclear waste liquid is 1BV / h~3BV / h.

[0034] The modified zirconium phosphate / resin composite material provided in the present application has at least the following advantages:

[0035] The modified zirconium phosphate / resin composite material provided in the present application includes modified zirconium phosphate and resin material. Among them, the resin material can provide physical support, increase the mechanical strength and stability of the composite material, so as to ensure its durability during the adsorption and recovery process of nuclides. And the porous structure of the resin material can increase the specific surface area, which helps to improve the adsorption performance.

[0036] Modified zirconium phosphate is zirconium phosphate containing doped metal ions. The layered structure of zirconium phosphate provides a large number of surface active sites for the adsorption and recovery of nuclides. And the addition of specific types of doped metal ions can change the interlayer charge distribution of zirconium phosphate or can form coordination bonds with nuclides, thereby enhancing the selectivity and adsorption capacity of the composite material for nuclides. In addition, the specific types of doped metal ions in the present application can balance the loading amount of metal ions and the layered structure of zirconium phosphate, so that the doped metal ions will not significantly change the interlayer distance of zirconium phosphate, so as to maintain the integrity of its layered structure and optimize the adsorption performance of the material.

[0037] Furthermore, the synergistic effect between the modified zirconium phosphate and the resin material in a specific mass ratio can not only give the composite material excellent radionuclide adsorption capacity, but also give the composite material excellent stability and porous structure, which enables the composite material provided in the present application to maintain structural and performance stability during multiple adsorption-regeneration cycles.

[0038] In summary, the modified zirconium phosphate / resin composite material provided in the present application has excellent adsorption and recovery performance for nuclides, and has good desorption and regeneration performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Actual photos of the modified zirconium phosphate and the modified zirconium phosphate / resin composite material prepared in Example 1 of the present application;

[0040] Figure 2 XRD diagrams of the modified zirconium phosphate prepared in Example 1 of the present application and the zirconium phosphate prepared in Comparative Example 1. DETAILED DESCRIPTION

[0041] The following is a further complete and clear description of the modified zirconium phosphate / resin composite material and its preparation method, and the method for recovering nuclides in nuclear waste liquid of the present application in combination with specific examples. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0042] In this application, "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of this application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0043] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. Unless otherwise specified or there is a contradiction, the terms or phrases used herein have the following meanings:

[0045] In the present application, "plurality", "multiple", "multiple times", "plurality", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0046] In this application, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0047] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0048] In the present application, references to “combinations thereof”, “any combination thereof”, “any combination thereof”, etc. include all suitable combinations of any two or more of the listed items.

[0049] In this application, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc. shall be based on the ability to implement the technical solution of this application, solve the technical problems of this application, and achieve the expected technical effects of this application.

[0050] In the present application, the terms “preferred”, “better”, “more preferred” and “suitable” are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute limitations on the scope of protection of the present application.

[0051] In the present application, the terms “further”, “furthermore”, “particularly”, etc. are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0052] In this application, "optionally", "optional" and "optional" refer to optional, that is, to any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0053] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1 to 10, indicating that t is any integer selected from the group of integers consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges included therein.

[0054] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0055] In the present application, the percentage content, unless otherwise specified, refers to mass percentage for solid-liquid mixing and solid-solid mixing, and volume percentage for liquid-liquid mixing.

[0056] In this application, when it comes to percentage concentration, unless otherwise specified, it refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.

[0057] In the production industries related to nuclear energy production, nuclear waste treatment and radioactive materials, adsorbent materials play an important role due to their unique physical and chemical properties. These materials are mainly used to control and reduce the emission of radioactive pollutants, ensure environmental safety, and support the safe operation of nuclear facilities. In the relevant technical fields, the main functions of adsorbent materials include: (1) preventing corrosion or deposit formation inside the reactor. (2) removing radioactive isotopes from radioactive gas and liquid waste, or capturing radioactive particles in the environment and reducing their radioactivity level for safe storage or disposal.

[0058] In the related art, there are two main types of improved adsorption materials: (1) tetrachloroaluminate modified type A molecular sieve adsorption material, which can adsorb cobalt ions, strontium ions and cesium ions. However, this method uses fly ash beads as the main raw material to prepare molecular sieves. Due to the physical and chemical properties of fly ash beads themselves, such as poor reactivity, poor mechanical strength and uneven structural composition, this adsorption material has the disadvantages of high pretreatment cost and poor regeneration performance. (2) Pure undoped zirconium phosphate material is used to adsorb nuclides. This adsorption material has limited adsorption capacity, resulting in poor adsorption and recovery effect of nuclides.

[0059] Based on this, in a first aspect of the present application, a modified zirconium phosphate / resin composite material is provided, wherein the modified zirconium phosphate / resin composite material comprises modified zirconium phosphate and a resin material in a mass ratio of 1:(0.05-0.2).

[0060] Wherein, the modified zirconium phosphate is zirconium phosphate containing doped metal ions, and the doped metal ions include Cu 2 + , Fe 3+ 、Zn 2+ 、Co 2+ and Ni 2+ One or more of .

[0061] The modified zirconium phosphate / resin composite material provided in the present application includes modified zirconium phosphate and resin material. Among them, the resin material can provide physical support, increase the mechanical strength and stability of the composite material, so as to ensure its durability during the adsorption and recovery process of nuclides. And the porous structure of the resin material can increase the specific surface area, which helps to improve the adsorption performance.

[0062] Modified zirconium phosphate is zirconium phosphate containing doped metal ions. The layered structure of zirconium phosphate provides a large number of surface active sites for the adsorption and recovery of nuclides. And the addition of specific types of doped metal ions can change the interlayer charge distribution of zirconium phosphate or can form coordination bonds with nuclides, thereby enhancing the selectivity and adsorption capacity of the composite material for nuclides. In addition, the specific types of doped metal ions in the present application can balance the loading amount of metal ions and the layered structure of zirconium phosphate, so that the doped metal ions will not significantly change the interlayer distance of zirconium phosphate, so as to maintain the integrity of its layered structure and optimize the adsorption performance of the material.

[0063] Furthermore, the synergistic effect between the modified zirconium phosphate and the resin material in a specific mass ratio can not only give the composite material excellent radionuclide adsorption capacity, but also give the composite material excellent stability and porous structure, which enables the composite material provided in the present application to maintain structural and performance stability during multiple adsorption-regeneration cycles.

[0064] In summary, the modified zirconium phosphate / resin composite material provided in the present application has excellent adsorption and recovery performance for nuclides, and has good desorption and regeneration performance.

[0065] It can be understood that in the present application, the mass ratio of the modified zirconium phosphate and the resin material included in the modified zirconium phosphate / resin composite material can be selected from any value between 1: (0.05~0.2). For example, the mass ratio of the modified zirconium phosphate and the resin material included in the modified zirconium phosphate / resin composite material includes but is not limited to 1: 0.05, 1: 0.08, 1: 0.09, 1: 0.1, 1: 0.11, 1: 0.12, 1: 0.13, 1: 0.15, 1: 0.18 or 1: 0.2, or within the range of any two of the above point values.

[0066] In one embodiment, the molar ratio of the doped metal ions to the zirconium ions in the zirconium phosphate is 1:(0.5-5). It is understandable that the molar ratio of the doped metal ions to the zirconium ions in the zirconium phosphate can be selected from any value between 1:(0.5-5). For example, the molar ratio of the doped metal ions to the zirconium ions in the zirconium phosphate includes but is not limited to 1:0.5, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5 or 1:5, or within the range of any two of the above point values.

[0067] The type of resin material plays an important role in ensuring its compatibility with the modified zirconium phosphate, so that the composite material has high efficiency and long-term stability in nuclide adsorption and regeneration. In one example, the resin material includes one or more of polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride, polystyrene and polyetheretherketone.

[0068] In one example, the doping metal ions include Zn 2+ .

[0069] The inventors of this application have found based on rich experience and a large number of experiments that when the doped metal ions include Zn 2+ When the composite material has better nuclide absorption and regeneration performance. 2+ The doping of Zn can moderately adjust the interlayer spacing of zirconium phosphate, thereby optimizing the pore structure and specific surface area of ​​the material to improve the adsorption capacity and selectivity. 2+ It also has strong coordination ability and can form stable coordination compounds with target nuclides, thereby enhancing the adsorption effect. 2+ It can form coordination bonds with oxygen atoms or other ligands in water to improve its ability to capture radioactive nuclides (especially rubidium ions and cesium ions). 2+ The chemical properties are relatively stable, which makes Zn 2+ The doped modified zirconium phosphate exhibits good stability during the adsorption and regeneration cycles and can maintain a high adsorption efficiency.

[0070] In a second aspect of the present application, there is provided a method for preparing the modified zirconium phosphate / resin composite material as described in any example of the first aspect of the present application, comprising the following steps:

[0071] S10, mixing a zirconium source, a phosphoric acid source and a doped metal salt in a dispersant by a hydrothermal method, and performing a reflux reaction to prepare a mixed solution.

[0072] S20, after solid-liquid separation of the mixed liquid, collecting the solid phase, washing the solid phase, and preparing the modified zirconium phosphate.

[0073] S30, mixing the modified zirconium phosphate in a solvent, adding a pore-forming agent and the resin material, and preparing a mixed slurry; wherein the mass ratio of the modified zirconium phosphate to the resin material is 1: (0.05-0.2).

[0074] S40, extruding the mixed slurry to prepare the modified zirconium phosphate / resin composite material.

[0075] In the preparation method provided by the present application, the zirconium source, the phosphate source and the doped metal salt can be uniformly dispersed and reacted by a hydrothermal method, so that a modified zirconium phosphate with uniform structure can be obtained. In addition, with the aid of solid-liquid separation and washing steps, impurities and residual reactants can be further removed to ensure the high purity of the modified zirconium phosphate and the high doping amount of doped metal ions. The modified zirconium phosphate, the resin material and the pore-forming agent are compounded to prepare a slurry, which can improve the fluidity and stability of the slurry, and improve the comprehensive properties of the final composite material such as stability and specific surface area. Furthermore, the preparation method of the composite material provided by the present application has simple steps, and the reaction conditions are relatively mild, which is suitable for industrial production.

[0076] In one example, in step S10, the doping metal salt includes the doping metal ions, and the phosphoric acid source does not include the doping metal ions.

[0077] In one example, in step S10, the molar ratio of the doped metal ions in the doped metal salt to the zirconium ions in the zirconium source is 1:(0.5~5). It can be understood that the molar ratio of the doped metal ions in the doped metal salt to the zirconium ions in the zirconium source can be selected from any value between 1:(0.5~5). For example, the molar ratio of the doped metal ions in the doped metal salt to the zirconium ions in the zirconium source includes but is not limited to 1:0.5, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5 or 1:5, or within the range of any two of the above point values.

[0078] In one example, in step S10, the process parameters for the reflux reaction include: the reaction temperature ≥ the boiling point of the dispersant, and the reaction time is 6h~18h.

[0079] The reaction temperature is higher than the boiling point of the dispersant, and the reactants are more easily dissolved and dispersed to form a more uniform precursor solution. In addition, it can provide sufficient energy to promote the chemical reaction between the zirconium source, the phosphoric acid source and the doped metal salt to generate a uniformly structured modified zirconium phosphate. In addition, limiting the reflux reaction time helps the doped metal ions to be evenly distributed in the layered structure of the zirconium phosphate to optimize the nuclide adsorption capacity of the composite material.

[0080] Furthermore, in step S10, the reaction temperature for the reflux reaction is in the range of the boiling point of the dispersant to 30° C. higher than the boiling point of the dispersant.

[0081] The type of zirconium source plays an important role in ensuring its solubility and dispersibility in the dispersant, controlling the reaction rate, and ensuring the crystal structure and porosity of the modified zirconium phosphate. In one example, in step S10, the zirconium source includes one or more of zirconium oxychloride, zirconium acetate, zirconium silicate, zirconium sulfate, and zirconium chloride.

[0082] In one example, in step S10, the phosphoric acid source includes one or more of sodium dihydrogen phosphate, ammonium dihydrogen phosphate, potassium dihydrogen phosphate, phosphorous acid, triethyl phosphate and sodium phosphate. + , which is different from doping metal elements. During the washing process, Na + can be effectively removed.

[0083] In one example, in step S10, the doped metal salt includes one or more of copper sulfate, iron sulfate, zinc sulfate, cobalt sulfate and nickel sulfate. The anions of the doped metal salt are all sulfate ions. Sulfate ions can be quickly removed during the washing process to reduce the residual amount of impurities in the modified zirconium phosphate. At this point, it can be understood that the main chemical components of the modified zirconium phosphate prepared after washing include: zirconium phosphate and doped metal ions doped in the zirconium phosphate layer structure.

[0084] In one example, in step S10, the molar ratio of the zirconium source, the phosphoric acid source and the doped metal salt is 1: (1-6): (1-5). It can be understood that the molar ratio of the zirconium source, the phosphoric acid source and the doped metal salt can be selected from any value between 1: (1-6): (1-5). For example, the molar ratio of the zirconium source, the phosphoric acid source and the doped metal salt includes but is not limited to 1: 1: 1, 1: 1.5: 1, 1: 1.8: 1, 1: 1.9: 1, 1: 2: 1, 1: 2: 1.1, 1: 2: 1.5, 1: 2: 2, 1: 2: 3, 1: 2: 4, 1: 2: 5, 1: 3: 1, 1: 4: 2, 1: 5: 3 or 1: 6: 4, or within the range of any two of the above point values.

[0085] In one example, in step S10, the dispersant includes one or more of water, ethanol, methanol, dimethyl sulfoxide and N,N-dimethylformamide.

[0086] In one example, in step S10, the mass ratio of the zirconium source to the dispersant is 1:(8-16). For example, the mass ratio of the zirconium source to the dispersant is 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15 or 1:16, or within the range of any two of the above point values.

[0087] It can be understood that in step S20, the washing step is mainly used to wash away the metal ions that may exist in the phosphoric acid source, as well as the anions in the zirconium source and the doped metal salt. Therefore, preferably, the phosphate does not include doped metal ions.

[0088] In one example, in step S20, the process parameters for washing include: washing with ethanol and water once or more times respectively.

[0089] In one example, the step of mixing the zirconium source, the phosphoric acid source and the doping metal salt in the dispersant by a hydrothermal method in step S20 includes:

[0090] After the zirconium source and phosphate are mixed in a dispersant by a hydrothermal method, the doping metal salt is added and mixed.

[0091] In one example, in step S30, the mass ratio of the modified zirconium phosphate and the solvent is 1:(1-8). For example, the mass ratio of the modified zirconium phosphate and the solvent includes but is not limited to 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7 or 1:8, or a range formed by any two of the above point values.

[0092] In one example, in step S30, the solvent includes one or more of water, ethanol, methanol, dimethyl sulfoxide and N,N-dimethylformamide.

[0093] In one example, in step S30, the pore-forming agent includes one or more of Tween 80, sodium bicarbonate, sodium chloride and polyethylene glycol.

[0094] In one example, in step S30, the resin material includes one or more of polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride, polystyrene and polyetheretherketone.

[0095] In one example, in step S30, the mass ratio of the modified zirconium phosphate and the pore-forming agent is 1:(0.03-0.15). For example, the mass ratio of the modified zirconium phosphate and the pore-forming agent includes but is not limited to 1:0.03, 1:0.04, 1:0.05, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, 1:0.11, 1:0.13 or 1:0.15, or within the range of any two of the above point values.

[0096] In step S40 of the present application, during the process of extruding the mixed slurry, the mixed slurry is dripped into water or acid solution using a syringe. At this time, the pore-forming agent can play a role, and there is no need for a high-temperature step to form holes.

[0097] In one specific example, the preparation method of the modified zirconium phosphate / resin composite material includes:

[0098] S100, after mixing the zirconium source and phosphate in a dispersant by a hydrothermal method, adding a doped metal salt to mix, performing a reflux reaction, collecting the solid phase after solid-liquid separation, and washing to prepare the modified zirconium phosphate. The process parameters for the reflux reaction include: the reaction temperature ≥ the boiling point of the dispersant, the reaction time is 6h~18h; the molar ratio of the zirconium source, the phosphate source and the doped metal salt is 1: (1~6): (1~5).

[0099] S200, mixing the modified zirconium phosphate in a solvent, adding a pore-forming agent and the resin material, and preparing a mixed slurry; wherein the mass ratio of the modified zirconium phosphate, the pore-forming agent and the resin material is 1: (0.03-0.15): (0.05-0.2).

[0100] S300, extruding the mixed slurry to prepare the modified zirconium phosphate / resin composite material.

[0101] In a third aspect of the present application, a method for recovering nuclides in nuclear waste liquid is provided, comprising the following steps:

[0102] P10. Use the modified zirconium phosphate / resin composite material described in any example of the first aspect of the present application to adsorb and treat nuclear waste liquid.

[0103] In one example, in step P10, the pH of the nuclear waste liquid is 6-9.

[0104] The modified zirconium phosphate / resin composite material provided in the present application has excellent acid and alkali resistance, and therefore has excellent pH applicability. It can be applied to nuclear waste liquid with a pH of 6 to 9. For example, the pH of the modified zirconium phosphate / resin composite material includes but is not limited to 6, 6.2, 6.5, 6.8, 7, 7.2, 7.5, 7.8, 8, 8.2, 8.5, 8.8 or 9, or within the range of any two of the above point values.

[0105] In one example, in step P10, the nuclear waste liquid includes one or more of rubidium ions and cesium ions.

[0106] The modified zirconium phosphate / resin composite material provided in the present application has excellent performance in adsorbing and recovering cesium ions and rubidium ions, and the composite material can be regenerated after adsorbing and recovering cesium ions and rubidium ions, has good repeatability, and has wide industrial application value.

[0107] In one example, in step P10, the process parameters of the adsorption treatment include: the flow rate of the nuclear waste liquid is 1BV / h~3BV / h.

[0108] The flow rate of the nuclear waste liquid can ensure that the nuclear waste liquid is evenly distributed in the adsorption column, and ensure that the adsorption material effectively contacts the nuclides in the nuclear waste liquid, thereby ensuring the adsorption and absorption efficiency. In addition, a flow rate of 1BV / h~3BV / h can maintain a reasonable processing time while ensuring a high adsorption efficiency, and will not cause the adsorption process to be too slow. For example, during the adsorption process, the flow rate of the nuclear waste liquid includes but is not limited to 1 BV / h, 1.5 BV / h, 1.8 BV / h, 2 BV / h, 2.2 BV / h, 2.5 BV / h, 2.8 BV / h or 3 BV / h, or within the range of any two of the above point values.

[0109] In one example, after the step of adsorption treatment of nuclear waste liquid, the following steps are further included:

[0110] P20. Desorb and regenerate the modified zirconium phosphate / resin composite material described in any example of the first aspect of the present application using a regeneration agent.

[0111] Illustratively, the regenerant includes, but is not limited to, one or more of ammonium chloride solution, hydrochloric acid, potassium chloride solution, and sodium chloride solution.

[0112] Furthermore, the mass concentration of the ammonium chloride solution is 15% to 30%.

[0113] The following further specific examples are provided to explain the present application in detail. It should also be understood that the following examples are only used to further explain the present application and cannot be understood as limiting the scope of protection of the present application. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present application belong to the scope of protection of the present application. The specific process parameters of the following embodiments are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not necessarily limited to the specific values ​​of the embodiments below.

[0114] Example 1

[0115] Embodiment 1 provides a modified zirconium phosphate / resin composite material and a preparation method thereof, comprising the following steps:

[0116] The preparation method of the modified zirconium phosphate / resin composite material comprises:

[0117] (1) Zirconium sulfate and sodium dihydrogen phosphate were mixed and stirred in water by a hydrothermal method for 1 hour, and then zinc sulfate (doped metal salt) was added and mixed, wherein the molar ratio of zirconium sulfate, sodium dihydrogen phosphate and zinc sulfate was 1:2:1, and the mass ratio of zirconium sulfate and water was 1:8; then the temperature was raised to 100°C and refluxed for 12 hours. The mixed solution after the reflux reaction was separated into solid and liquid by suction filtration, and the obtained filter cake was washed with ethanol and water for multiple times to wash away the residual metal ions (Na + ) and sulfate ions, and then transferred to an oven for drying at 80° C., crushed and passed through a 200-mesh sieve to prepare the modified zirconium phosphate.

[0118] (2) The modified zirconium phosphate and dimethyl sulfoxide were mixed and stirred for 0.5 h, Tween 80 (pore-forming agent) was added, and the stirring was continued for 0.5 h, and then polyvinylidene fluoride (resin material) was added, and the stirring was continued for 2 h to prepare a mixed slurry; wherein the mass ratio of the modified zirconium phosphate, Tween 80 and polyvinylidene fluoride was 1:0.05:0.1, and the mass ratio of the modified zirconium phosphate and dimethyl sulfoxide was 1:2.

[0119] (3) The mixed slurry is placed in a cylindrical needle tube, and the mixed slurry is extruded by an air compressor to obtain a uniform modified zirconium phosphate / resin composite material. The modified zirconium phosphate / resin composite material is a spherical particle adsorption material. The actual picture of the modified zirconium phosphate and the modified zirconium phosphate / resin composite material prepared in Example 1 is as follows: Figure 1 shown.

[0120] Example 2

[0121] Embodiment 2 provides a modified zirconium phosphate / resin composite material and a preparation method thereof, comprising the following steps:

[0122] The preparation method of the modified zirconium phosphate / resin composite material comprises:

[0123] (1) Zirconium sulfate and sodium dihydrogen phosphate were mixed and stirred in water by a hydrothermal method for 1 hour, and copper sulfate (doped metal salt) was added and mixed, wherein the molar ratio of zirconium sulfate, sodium dihydrogen phosphate and copper sulfate was 1:2:1, and the mass ratio of zirconium sulfate and water was 1:8; then the temperature was raised to 100°C and refluxed for 12 hours. The mixed solution after the reflux reaction was separated into solid and liquid by suction filtration, and the obtained filter cake was washed with ethanol and water for multiple times to wash away the residual metal ions (Na + ) and sulfate ions, and then transferred to an oven for drying at 80° C., crushed and passed through a 200-mesh sieve to prepare the modified zirconium phosphate.

[0124] (2) The modified zirconium phosphate and dimethyl sulfoxide were mixed and stirred for 0.5 h, Tween 80 was added, and the stirring was continued for 0.5 h, and then polyvinylidene fluoride (resin material) was added and the stirring was continued for 2 h to prepare a mixed slurry; wherein the mass ratio of the modified zirconium phosphate, Tween 80 and polyvinylidene fluoride was 1:0.05:0.1, and the mass ratio of the modified zirconium phosphate and dimethyl sulfoxide was 1:2.

[0125] (3) The mixed slurry is placed in a cylindrical needle tube, and an air compressor is used to extrude the mixed slurry to obtain a uniform modified zirconium phosphate / resin composite material, wherein the modified zirconium phosphate / resin composite material is a spherical particle adsorption material.

[0126] Example 3

[0127] Example 3 provides a modified zirconium phosphate / resin composite material and a preparation method thereof, comprising the following steps:

[0128] The preparation method of the modified zirconium phosphate / resin composite material comprises:

[0129] (1) Zirconium sulfate and sodium dihydrogen phosphate were mixed and stirred in water by a hydrothermal method for 1 hour, and then zinc sulfate (doped metal salt) was added and mixed, wherein the molar ratio of zirconium sulfate, sodium dihydrogen phosphate and zinc sulfate was 1:2:1, and the mass ratio of zirconium sulfate and water was 1:8; then the temperature was raised to 100°C and refluxed for 12 hours. The mixed solution after the reflux reaction was separated into solid and liquid by suction filtration, and the obtained filter cake was washed with ethanol and water for multiple times to wash away the residual metal ions (Na + ) and sulfate ions, and then transferred to an oven for drying at 80° C., crushed and passed through a 200-mesh sieve to prepare the modified zirconium phosphate.

[0130] (2) The modified zirconium phosphate and dimethyl sulfoxide were mixed and stirred for 0.5 h, polyethylene glycol was added, and the stirring was continued for 0.5 h, and then polyacrylonitrile (resin material) was added and the stirring was continued for 2 h to prepare a mixed slurry; wherein the mass ratio of the modified zirconium phosphate, polyethylene glycol and polyacrylonitrile was 1:0.05:0.1, and the mass ratio of the modified zirconium phosphate and dimethyl sulfoxide was 1:2.

[0131] (3) The mixed slurry is placed in a cylindrical needle tube, and an air compressor is used to extrude the mixed slurry to obtain a uniform modified zirconium phosphate / resin composite material, wherein the modified zirconium phosphate / resin composite material is a spherical particle adsorption material.

[0132] Example 4

[0133] Example 4 is substantially the same as Example 1, the main difference being that in Example 4, iron sulfate is selected as the doping metal salt.

[0134] Example 5

[0135] Example 5 is substantially the same as Example 1, the main difference being that in Example 5, cobalt sulfate is selected as the doping metal salt.

[0136] Example 6

[0137] Example 6 is substantially the same as Example 1, the main difference being that nickel sulfate is selected as the doping metal salt in Example 6.

[0138] Comparative Example 1

[0139] Comparative Example 1 is substantially the same as Example 1, except that zinc sulfate is not added in Comparative Example 1. The specific steps include:

[0140] The preparation method of the adsorption material comprises:

[0141] (1) Zirconium sulfate and sodium dihydrogen phosphate were mixed and stirred in water by a hydrothermal method for 1 hour, wherein the molar ratio of zirconium sulfate to sodium dihydrogen phosphate was 1:2, and the mass ratio of zirconium sulfate to water was 1:8; then the temperature was raised to 100°C and refluxed for 12 hours. The mixed solution after the reflux reaction was separated into solid and liquid by suction filtration, and the obtained filter cake was washed with ethanol and water for multiple times to wash away the residual metal ions (Na + ) and sulfate ions, and then transferred to an oven for drying at 80°C, crushed and passed through a 200-mesh sieve to prepare zirconium phosphate.

[0142] (2) Mix zirconium phosphate and dimethyl sulfoxide and stir for 0.5 h, add Tween 80, continue stirring for 0.5 h, then add polyvinylidene fluoride (resin material), continue stirring for 2 h, and prepare a mixed slurry; wherein the mass ratio of zirconium phosphate, Tween 80 and polyvinylidene fluoride is 1:0.05:0.1, and the mass ratio of zirconium phosphate and dimethyl sulfoxide is 1:2.

[0143] (3) The mixed slurry is placed in a cylindrical needle tube, and the mixed slurry is squeezed out by an air compressor to obtain a uniform spherical particle adsorption material.

[0144] Comparative Example 2

[0145] Comparative Example 2 is basically the same as Example 1, with the main difference being that: Comparative Example 2 uses commercially available α-zirconium phosphate powder to replace the modified zirconium phosphate / resin composite material in Example 1. The specific steps include:

[0146] (2) Mix commercially available α-zirconium phosphate powder and dimethyl sulfoxide and stir for 0.5 h, add Tween 80, continue stirring for 0.5 h, then add polyvinylidene fluoride (resin material) and continue stirring for 2 h to prepare a mixed slurry; wherein the mass ratio of the commercially available zirconium phosphate powder, Tween 80 and polyvinylidene fluoride is 1:0.05:0.1, and the mass ratio of the commercially available zirconium phosphate powder and dimethyl sulfoxide is 1:2.

[0147] (3) The mixed slurry is placed in a cylindrical needle tube, and the mixed slurry is squeezed out by an air compressor to obtain a uniform spherical particle adsorption material.

[0148] The XRD patterns of the modified zirconium phosphate and zirconium phosphate prepared in Example 1 and Comparative Example 1 are as follows: Figure 2 As shown. Figure 2 It can be seen that the peak shape of the modified zirconium phosphate prepared in Example 1 has changed, indicating the successful doping of metallic zinc.

[0149] The spherical particle adsorption materials prepared in the above examples and comparative examples were tested for nuclide adsorption performance, and the specific steps included:

[0150] 10 mL of the spherical particle adsorption material of the embodiment and the comparative example was filled into a glass chromatography column to treat 20 BV of wastewater, wherein the wastewater was laboratory-made wastewater with a pH of 7.68, and the elements and contents contained in the wastewater were: Rb 140.25 ppm, Cs 101.28 ppm, Li 151.40 ppm, Na 13760 ppm, Mg 190.96 ppm, K 346.12 ppm, Ca 231.83 ppm. The flow rate of the adsorption treatment was controlled to be 2 BV / h, and the rubidium and cesium content in the wastewater after adsorption treatment was determined using ICP, and the results are shown in Table 1.

[0151] Table 1

[0152]

[0153] It can be clearly seen from Table 1 that the adsorption materials prepared in Examples 1 to 6 of the present application have excellent adsorption performance for rubidium ions and cesium ions. Among them, the adsorption recovery performance of the adsorption material prepared by zinc-doped modified zirconium phosphate and polyvinylidene fluoride in Example 1 is even better.

[0154] Using a 20% NH4Cl solution as a regeneration agent, the adsorbent material in the above-mentioned embodiments and comparative examples after the first adsorption treatment was desorbed and regenerated, and the Rb and Cs contents in the first effluent were recorded. Then the regenerated adsorbent material adsorbed the above-mentioned wastewater for a second adsorption treatment, and after desorption and regeneration under the same conditions, the Rb and Cs contents of the second effluent were recorded. The adsorbent material after the second regeneration was adsorbed the above-mentioned wastewater for a third adsorption treatment, and then desorption and regeneration under the same conditions were performed, and the Rb and Cs contents of the third effluent were recorded. The average regeneration rate of the adsorbent material in the embodiments and comparative examples was calculated based on the Rb and Cs contents in the first effluent, the Rb and Cs contents in the second effluent, and the Rb and Cs contents in the third effluent. The corresponding average regeneration rate is calculated as: [(Rb and Cs content in the first effluent / Rb and Cs content adsorbed in the first adsorption treatment) + (Rb and Cs content in the second effluent / Rb and Cs content adsorbed in the second adsorption treatment) + (Rb and Cs content in the third effluent / Rb and Cs content adsorbed in the third adsorption treatment)] / 3.

[0155] The average regeneration rate data of the adsorbent material obtained after repeating desorption and adsorption three times are shown in Table 2.

[0156] Table 2

[0157]

[0158] From Table 2, it can be clearly seen that the spherical particle adsorption materials prepared in Examples 1 to 3 of the present application have excellent regeneration performance compared with Comparative Examples 1 to 2. Among Examples 1 to 3, the adsorption material prepared by zinc-doped modified zirconium phosphate and polyvinylidene fluoride in Example 1 has the highest regeneration rate.

[0159] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0160] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. A modified zirconium phosphate / resin composite material, characterized in that: The modified zirconium phosphate / resin composite material comprises modified zirconium phosphate and resin material in a mass ratio of 1:(0.05-0.2); Wherein, the modified zirconium phosphate is zirconium phosphate containing doped metal ions, and the doped metal ions include Cu 2+ , Fe 3 + 、Zn 2+ 、Co 2+ and Ni 2+ One or more of .

2. The modified zirconium phosphate / resin composite material according to claim 1, characterized in that: The molar ratio of the doped metal ions to the zirconium ions in the zirconium phosphate is 1:(0.5-5).

3. The modified zirconium phosphate / resin composite material according to claim 1, characterized in that: The resin material includes one or more of polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride, polystyrene and polyetheretherketone.

4. The modified zirconium phosphate / resin composite material according to any one of claims 1 to 3, characterized in that: The doping metal ions include Zn 2+ .

5. A method for preparing the modified zirconium phosphate / resin composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing a zirconium source, a phosphate source and a doping metal salt in a dispersant by a hydrothermal method, and performing a reflux reaction to prepare a mixed solution, wherein the doping metal salt includes the doping metal ion; After the mixed liquid is separated into solid and liquid, the solid phase is collected, and after the solid phase is washed, the modified zirconium phosphate is prepared; The modified zirconium phosphate is mixed in a solvent, and a pore-forming agent and the resin material are added to prepare a mixed slurry, wherein the mass ratio of the modified zirconium phosphate to the resin material is 1: (0.05-0.2); The mixed slurry is extruded to prepare the modified zirconium phosphate / resin composite material.

6. The method for preparing the modified zirconium phosphate / resin composite material according to claim 5, characterized in that: The process parameters for the reflux reaction include: reaction temperature ≥ boiling point of the dispersant, and reaction time of 6h~18h.

7. The method for preparing the modified zirconium phosphate / resin composite material according to claim 5 or 6, characterized in that: The steps of preparing the mixed solution have one or more of the following characteristics: (1) The zirconium source includes one or more of zirconium oxychloride, zirconium acetate, zirconium silicate, zirconium sulfate and zirconium chloride; (2) The phosphoric acid source includes one or more of sodium dihydrogen phosphate, ammonium dihydrogen phosphate, potassium dihydrogen phosphate, phosphorous acid, triethyl phosphate and sodium phosphate; (3) The doped metal salt includes one or more of copper sulfate, iron sulfate, zinc sulfate, cobalt sulfate and nickel sulfate; (4) The molar ratio of the zirconium source, the phosphoric acid source and the doping metal salt is 1:(1-6):(1-5); (5) The dispersant includes one or more of water, ethanol, methanol, dimethyl sulfoxide and N,N-dimethylformamide; (6) The mass ratio of the zirconium source and the dispersant is 1:(8-16).

8. The method for preparing the modified zirconium phosphate / resin composite material according to claim 5 or 6, characterized in that: The steps of preparing the mixed slurry have one or more of the following characteristics: (1) The mass ratio of the modified zirconium phosphate to the solvent is 1:(1-8); (2) The solvent includes one or more of water, ethanol, methanol, dimethyl sulfoxide and N,N-dimethylformamide; (3) The pore-forming agent includes one or more of Tween 80, sodium bicarbonate, sodium chloride and polyethylene glycol; (4) The resin material includes one or more of polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride, polystyrene and polyetheretherketone; (5) The mass ratio of the modified zirconium phosphate to the pore-forming agent is 1:(0.03-0.15).

9. A method for recovering nuclides from nuclear waste liquid, characterized in that: The following steps are involved: The modified zirconium phosphate / resin composite material according to any one of claims 1 to 4 is used to adsorb and treat nuclear waste liquid.

10. The method for recovering nuclides in nuclear waste liquid according to claim 9, characterized in that: The step of adsorbing the nuclear waste liquid has one or more of the following characteristics: (1) The pH of the nuclear waste liquid is 5 to 10; (2) The nuclear waste liquid contains one or more of rubidium ions and cesium ions; (3) The process parameters of the adsorption treatment include: the flow rate of the nuclear waste liquid is 1BV / h~3BV / h.

Citation Information

Patent Citations

  • Preparation method and application method of CuZr(PO4)2*4H2O material

    CN103072965A

  • Caesium selective absorbent and preparation method thereof

    CN103831090A

Cited By

  • Amphoteric nuclear-grade ion exchange resin as well as preparation method and application thereof

    CN121537579A